ANALISIS PERAN PERPUSTAKAAN UMUM SEBAGAI RUANG PUBLIK DARI PERSPEKTIF TEORI SOSIAL PUBLIC SPHERE JURGEN HABERMAS - Septevan Nanda Yudisman (Maktabatuna, 2020)
Public libraries play a uniquely important role in an industrial neutral society, libraries provide information and differing views on a scene. The public can find out without coercion about the latest issues that concern them. This invaluable role and provision of fresh ideas is perhaps the greatest service to society that libraries provide and that no other type of institution can fulfill. Through libraries, people can empower themselves by obtaining a variety of information in accordance with the needs of their profession and their respective fields of work. Public space is inseparable from the ideas carried by a famous philosopher in Germany, namely Jurgen Habermas. The idea of public space is an idea that he popularized, that the public space is a medium for communicating information and views. As depicted in England and France, people meet, chat, discuss about new books published or new works of art being created. The public space is a medium for communicating information and views are very relevant to the role of the library as a medium of communication between authors through books or their writings and readers. In other words, the library is one of the communication media as expressed by Habermas regarding public space.